2012
DOI: 10.1155/2012/426278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Speed Power Training on Muscle Performance and Braking Speed in Older Adults

Abstract: We examined whether high-speed power training (HSPT) improved muscle performance and braking speed using a driving simulator. 72 older adults (22 m, 50 f; age = 70.6 ± 7.3 yrs) were randomized to HSPT at 40% one-repetition maximum (1RM) (HSPT: n = 25; 3 sets of 12–14 repetitions), slow-speed strength training at 80%1RM (SSST: n = 25; 3 sets of 8–10 repetitions), or control (CON: n = 22; stretching) 3 times/week for 12 weeks. Leg press and knee extension peak power, peak power velocity, peak power force/torque,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…It may be that greater improvements in muscle power and velocity observed in HSPT simply did not transfer to typical mobility-based functional tasks; therefore, positive transfer of power and speed to function may require novel functional tasks performed at higher speeds. In a previous study, we did find that HSPT demonstrated a transfer of power and velocity to function when the high-speed functional movements (braking speed on a driving simulator) were similar to the nature of the high-speed training (LP exercise) (20). A limitation of the present study was that our choice of functional assessments may not have adequately allowed for the functional impact of power training and that more power and speed-related functional tasks should have been included.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It may be that greater improvements in muscle power and velocity observed in HSPT simply did not transfer to typical mobility-based functional tasks; therefore, positive transfer of power and speed to function may require novel functional tasks performed at higher speeds. In a previous study, we did find that HSPT demonstrated a transfer of power and velocity to function when the high-speed functional movements (braking speed on a driving simulator) were similar to the nature of the high-speed training (LP exercise) (20). A limitation of the present study was that our choice of functional assessments may not have adequately allowed for the functional impact of power training and that more power and speed-related functional tasks should have been included.…”
Section: Discussionmentioning
confidence: 86%
“…Using an intent-to-treat design, the data from 33 participants (HSPT: n ϭ 12, SSST: n ϭ 10, and CON: n ϭ 11) were analyzed in this study. Twenty of these 33 participants were part of a previous study on muscle performance (20). The muscle performance, function, and pain data reported in the present study, however, are unique to these 33 participants and have not been reported elsewhere.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Peak power is typically determined by measuring power output at several percentages of the one-repetition maximum (1RM) (3,6,7,8,10,18,19), and choosing the highest power output value across that range of external resistances. Power typically increases as external resistance is increased, reaching a peak between 60-70% 1RM in this population (10) and decreasing at the highest external resistances (10,19,20,21). …”
Section: Introductionmentioning
confidence: 88%
“…Numerous studies have investigated training programs to keep older drivers safe drivers and to postpone or even counteract functional and driving impairment. Various studies have investigated direct types of training of driving ability through for example simulator training (Casutt, Theill, Martin, Keller, & Jäncke, 2014;Romoser & Fisher, 2009) and indirect types of training of driving ability through training of functional abilities, such as motor abilities (Marmeleira, Godinho, & Fernandes, 2009;Sayers & Gibson, 2012) and cognitive abilities (Ball, Edwards, Ross, & McGwin, 2010;Cassavaugh & Kramer, 2009). However, only if the variance explained by functional abilities is sufficiently high, will a training of functional abilities be successful in training driving ability.…”
Section: Introductionmentioning
confidence: 99%